2017
DOI: 10.1111/jfs.12332
|View full text |Cite
|
Sign up to set email alerts
|

Response surface model for the reduction of Salmonella biofilm on stainless steel with lactic acid, ethanol, and chlorine as controlling factors

Abstract: A disinfectant containing chlorine (Cl), ethanol (EtOH), and lactic acid (LA) was investigated to reduce Salmonella biofilm on stainless steel. The present experiment was employed with disinfectants: Cl (50, 100, 150 ppm), LA (1, 2, and 3%), EtOH (10, 20, and 30%) and exposure times (ET; .5, 2, 3.5 min). A response surface model developed to predict the reduction of Salmonella biofilms was found to be significant (p < .0001) with a regression coefficient of .8019 and an insignificant lack of fit (p = .364). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This research found that both chlorine-based compositions can effectively reduce the number of planktonic cells and biofilms of Salmonella enteritidis on food contact surfaces. In addition, some studies examined the effectiveness of alcohol-based disinfectants, namely ethanol with a mixture of chlorine and lactic acid, against several Salmonella serotypes on stainless steel surfaces conducted by Zhang [6]. Based on the observations, it was concluded that the ethanol-based disinfectant mixture was effective in reducing the presence of Salmonella on stainless steel surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…This research found that both chlorine-based compositions can effectively reduce the number of planktonic cells and biofilms of Salmonella enteritidis on food contact surfaces. In addition, some studies examined the effectiveness of alcohol-based disinfectants, namely ethanol with a mixture of chlorine and lactic acid, against several Salmonella serotypes on stainless steel surfaces conducted by Zhang [6]. Based on the observations, it was concluded that the ethanol-based disinfectant mixture was effective in reducing the presence of Salmonella on stainless steel surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial cells in biofilm show higher antibiotic resistance and survive longer than planktonic cells (Wijman, Leeuw, Moezelaar, Zwietering, & Abee, ). Once biofilms are formed, bacteria are difficult to remove completely (Zhang, Ye, Juneja, & Xu, ). Hence, the contamination and antibiotic resistance of B. subtilis on food contact surfaces and food‐processing equipment increase due to their biofilm‐forming capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Also, RSM was used to investigate the influence of the concentration of sodium chloride, calcium chloride, and urea in reducing biofilm formation by B. cereus (Ranmadugala et al, 2017). A predictive model for estimating the removal of Salmonella biofilm in SS coupons was obtained using various concentrations of chlorine (50-150 ppm), ethanol (10-30%), and lactic acid (1-3%) (Zhang et al, 2017). RSM was also used to build a model to predict reductions in uropathogenic Escherichia coli biofilms using the combination of cranberry extract (3-9%), caprylic acid (0.01-0.05%) and thymol (0.01-0.5%) (Kim & Rhee, 2018).…”
Section: Biofilmmentioning
confidence: 99%
“…Response surface methodology (RSM) is recognized as a powerful gathering tool of mathematical and statistical approaches which are helpful to analyze and model problems, where a response of interest is affected by multiple independent variables for response optimization (Montgomery, 2005;Chelladurai et al, 2021). The RSM has been used as a mathematical strategy to predict the inactivation of monospecies biofilm from different microorganisms (Kim & Rhee, 2018;Ranmadugala, Ebrahimnezhad, Manley-Harris, Ghasemi, & Berenjian, 2017;Zhang, Ye, Juneja, & Xu, 2017). Nevertheless, to our knowledge, no study has modeled the removal of multispecies biofilm, especially using the RSM.…”
Section: Introductionmentioning
confidence: 99%